Respuesta :
ANSWER
The completely factored form is
[tex]2(2x + 5)(2x - 5)[/tex]
EXPLANATION
The given expression is
[tex]8 {x}^{2} - 50[/tex]
We factor the highest common factor to get,
[tex]2( {4x}^{2} - 25)[/tex]
We can rewrite the expression in the parenthesis as difference of two squares.
[tex]2( {(2x)}^{2} - {5}^{2} )[/tex]
Recall that,
[tex] {a}^{2} - {b}^{2} = (a + b)(a-b)[/tex]
This implies that,
[tex]2(2x + 5)(2x - 5)[/tex]
The correct answer is option D.
The completely factored form is
[tex]2(2x + 5)(2x - 5)[/tex]
EXPLANATION
The given expression is
[tex]8 {x}^{2} - 50[/tex]
We factor the highest common factor to get,
[tex]2( {4x}^{2} - 25)[/tex]
We can rewrite the expression in the parenthesis as difference of two squares.
[tex]2( {(2x)}^{2} - {5}^{2} )[/tex]
Recall that,
[tex] {a}^{2} - {b}^{2} = (a + b)(a-b)[/tex]
This implies that,
[tex]2(2x + 5)(2x - 5)[/tex]
The correct answer is option D.
Answer:
The factored form of 8x² – 50 is 2 (2x +5)(2x -5) .
Step-by-step explanation:
As given the expression in the question be as follow.
= 8x² - 50
= 2 (4x² - 25)
As
4x² = (2x)²
25 = 5²
Put above values in the expression
= 2 ((2x)² - 5²)
By using the property
(a² - b²) = (a + b)(a - b)
As
a = 2x
b = 5
Thus
= 2 (2x +5)(2x - 5)
Therefore the factored form of 8x² – 50 is 2 (2x +5)(2x -5) .